Development of a Game-Based Mobile Application to Improve the Psychosocial Well-Being of Children with Cancer and Their Caregivers - Virdiyanti, Ruri; Maulidah; Neisya Sa'adatul Ula, Luthfiyah; Afriliani, Asyifa; Amelia Sar, Citra (Yayasan Rumah Ilmu Professor, 2025)
Pediatric cancer not only impacts children physically but also significantly affects their psychosocial well-being and that of their caregivers. Traditional play therapy has been widely used to address psychological distress in young patients, but digital transformation opens new avenues to enhance its accessibility and effectiveness. This study aims to develop and evaluate a mobile application-based game to support the psychosocial health of children with cancer and their caregivers. The research adopted a design-based approach involving need analysis, app development, and usability testing. The application includes interactive education about cancer, relaxation exercises, and caregiver support communities. Effectiveness was assessed through a pre-and post-use evaluation involving children undergoing cancer treatment and their caregivers in selected hospitals. Significant improvements were found post-intervention: children experienced a 50% decrease in anxiety and a 47.3% improvement in mood; caregivers reported reduced stress (33.7%) and a 53.9% increase in perceived social support. Both children and caregivers expressed high satisfaction and willingness to continue using the app. The developed mobile application positively impacts the emotional resilience and psychosocial conditions of pediatric cancer patients and their caregivers. Integrating play therapy into a digital format provides an accessible, engaging, and effective tool to enhance quality of life during treatment.